A gradient-damage model for amorphous glassy polymers: Consistent formulation of viscoplasticity and damage evolution in a micromorphic framework - Hamdoun, Ayoub; Mahnken, Rolf; Ostwald, Richard (European Journal of Mechanics / A Solids)

Prädiktoren der persönlichen Verpflichtung in Eltern-Kind-Beziehungen im Erwachsenenalter - Schönert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Entwicklungspsychologie und Pädagogische Psychologie)

Discrete Diffusion-Based Model-Level Explanation of Heterogeneous GNNs with Node Features - Das, Pallabee; Heindorf, Stefan (Proceedings of the ACM Web Conference 2026 (WWW ’26))
Many real-world datasets, such as citation networks, social networks, and molecular structures, are naturally represented as heterogeneous graphs, where nodes belong to different types and have additional features. For example, in a citation network, nodes representing "Paper" or "Author" may include attributes like keywords or affiliations. A critical machine learning task on these graphs is node classification, which is useful for applications such as fake news detection, corporate risk assessment, and molecular property prediction. Although Heterogeneous Graph Neural Networks (HGNNs) perform well in these contexts, their predictions remain opaque. Existing post-hoc explanation methods lack support for actual node features beyond one-hot encoding of node type and often fail to generate realistic, faithful explanations. To address these gaps, we propose DiGNNExplainer, a model-level explanation approach that synthesizes heterogeneous graphs with realistic node features via discrete denoising diffusion. In particular, we generate realistic discrete features (e.g., bag-of-words features) using diffusion models within a discrete space, whereas previous approaches are limited to continuous spaces. We evaluate our approach on multiple datasets and show that DiGNNExplainer produces explanations that are realistic and faithful to the model's decision-making, outperforming state-of-the-art methods.

Navigating the dual nature: do explainers adapt to explainee interests when explaining technical artifacts - Lutz, Terfloth; Buhl, Heike M.; Lohmer, Vivien; Kern, Friederike; Schaffer, Michael E.; Schulte, Carsten (International Journal of Technology and Design Education)

Von Baumdaten zu Datenwäldern. Eine Umweltgeschichte der Informationsverarbeitung im Ausklang des langen 19. Jahrhunderts - Schmitt, Martin (Rechnen, Zeichnen, Reden Zur Geschichte der Datenverarbeitung im langen 19. Jahrhundert)
Keywords: Umweltgeschichte; 19. Jahrhundert; Deutschland; Forstwirtschaft; Konrad Zuse; Datenverarbeitung; Umweltdaten

When prediction replaces explanation: A threat to psychological science - Knauff, Markus; Butz, Martin V.; Kaup, Barbara; Kunde, Wilfried; Scharlau, Ingrid (psyarxiv)
Keywords: explainability; explanation; prediction

Predicting states of understanding in explanatory interactions using cognitive load-related linguistic cues - Wang, Yu; Türk, Olcay; Grimminger, Angela; Buschmeier, Hendrik (Proceedings of the 15th Language Resources and Evaluation Conference)
We investigate how verbal and nonverbal linguistic features, exhibited by speakers and listeners in dialogue, can contribute to predicting the listener's state of understanding in explanatory interactions on a moment-by-moment basis. Specifically, we examine three linguistic cues related to cognitive load and hypothesised to correlate with listener understanding: the information value (operationalised with surprisal) and syntactic complexity of the speaker's utterances, and the variation in the listener's interactive gaze behaviour. Based on statistical analyses of the MUNDEX corpus of face-to-face dialogic board game explanations, we find that individual cues vary with the listener's level of understanding. Listener states (‘Understanding’, ‘Partial Understanding’, ‘Non-Understanding’ and ‘Misunderstanding’) were self-annotated by the listeners using a retrospective video-recall method. The results of a subsequent classification experiment, involving two off-the-shelf classifiers and a fine-tuned German BERT-based multimodal classifier, demonstrate that prediction of these four states of understanding is generally possible and improves when the three linguistic cues are considered alongside textual features.

The Intersection Distribution: New Results and Perspectives - Klawuhn, Lukas-André Dominik; Huczynska, Sophie; Paterson, Maura (Finite Fields and Their Applications)
Intersection distribution and non-hitting index are concepts introduced recently by Li and Pott as a new way to view the behaviour of a collection of finite field polynomials. With both an algebraic interpretation via the intersection of a polynomial with a set of lines, and a geometric interpretation via a (q+1)-set possessing an internal nucleus, the concepts have proved their usefulness as a new way to view various long-standing problems, and have applications in areas such as Kakeya sets. In this paper, by exploiting connections with diverse areas including the theory of algebraic curves, cyclotomy and the enumeration of irreducible polynomials, we establish new results and resolve various Open Problems of Li and Pott. We prove geometric results which shed new light on the relationship between intersection distribution and projective equivalence of polynomials, and algebraic results which describe and characterise the degree of Sf - the index of the largest non-zero entry in the intersection distribution of f. We provide new insights into the non-hitting spectrum, and show the limitations of the non-hitting index as a tool for characterisation. Finally, the benefits provided by the connections to other areas are evidenced in two short new proofs of the cubic case.

Einleitung: Alles fließt - Spener, Anna Maria (WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien. Sammelband zur fünften studentischen Tagung des Fachbereichs Komparatistik an der Universität Paderborn)

Nasses Land: Wetlands als relationale Räume gegenhegemonialer Wissensproduktion in der künstlerischen Forschung - Spener, Anna Maria (WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien)

WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien. Sammelband zur fünften studentischen Tagung des Fachbereichs Komparatistik an der Universität Paderborn

Discounted Sales of Expiring Perishables: Challenges for Demand Forecasting in Grocery Retail Practice - Winkelmann, David; Elbracht, Theresa; Brenker, Jonas Maximilian; Gerzen, Arnold (arXiv:2602.04464)
Grocery retailers frequently apply price discounts to stimulate demand for expiring perishables. However, integrating these discounted sales into future demand forecasts presents a significant challenge. This study investigates the effectiveness of incorporating a fixed share of these sales as regular demand into the forecast, as commonly applied in practice. We employ a two-step regression approach on data from a major European grocery retailer, covering over 1,700 products across 676 stores. We reveal that forecasts underestimate actual demand for most SKUs when discounted sales occur. This residual uplift effect is significantly influenced by the number of sales at reduced prices. Our findings underscore the necessity for more precise approaches to integrate discounted sales into demand forecasts, thereby preventing excess inventory and the associated economic and environmental impacts of spoilage in the grocery sector.

Artificial intelligence in digital service ecosystems—Towards a taxonomy and archetypes - Hansmeier, Philipp; Schäfer, Jannika Marie; zur Heiden, Philipp (Electronic Markets)
Traditional dyadic customer-provider interactions are being shifted to polyadic interactions involving diverse participants in digital service ecosystems. Especially, artificial intelligence (AI) is increasingly integrated into these ecosystems, so that they comprise non-human participants (e.g., AI-based chatbots)—fundamentally altering the nature of value (co-)creation. While existing literature examines human-to-human interactions, knowledge of service interactions between human actors and AI-based systems is still underexplored. To address this research gap, we develop a taxonomy, comprising six iterations, that explores the peculiarities of AI as either a resource or a (non-human) agent in digital service ecosystems. We evaluate our taxonomy using a multiple case study and derive the four archetypes of AI in digital service ecosystems: (1) discriminative experience enhancer, (2) protective ecosystem orchestrator, (3) ecosystem innovation companion, and (4) personalized service composer. Our results extend the knowledge on service science by showing how AI-based systems—discriminative or generative, and focusing on the interaction in the ecosystem or the individual service encounter—assume the role of resources and non-human agents. Researchers and practitioners can utilize our results to augment their ecosystems with AI.

Towards a Service Ecosystem Perspective on Customer Experience: Insights from Hybrid (Online-Offline) Customer Journeys - Hansmeier, Philipp; zur Heiden, Philipp (Behaviour & Information Technology)

Ultra-Broadband Photonically Assisted Analog-to-Digital-Converters - Witzens, Jeremy; Drayss, Daniel; Fang, Dengyang; Moscoso Mártir, Alvaro; Müller, Juliana; Weizel, Maxim; Zazzi, Andrea; Freude, Wolfgang; Koos, Christian; Randel, Sebastian; Scheytt, J. Christoph (Electronic-Photonic Integrated Systems for Ultrafast Signal Processing)
We present recent progress made towards ultra-broadband photonically assisted analog-to-digital converters, that leverage both the low jitter of best-of-class mode-locked lasers as well as the capability of optics to break down broadband signals into multiple lower speed tributaries that can be better handled by electronics. We review in particular our work on both time- and frequency-domain approaches and give an outlook on how these architectures can be extended to include further signal processing tasks such as equalization. Optically triggered track-and-hold amplifiers are reported with an equivalent jitter below 80 fs rms in a signal frequency range from 20 GHz to 70 GHz. Frequency-domain architectures implementing optical arbitrary waveform measurement up to signal bandwidths of 610 GHz are also shown. Finally, an architecture allowing the deserialization and equalization of PAM4 signals is introduced and modeled for operation in 400 Gb/s links.

Integrated Photonic-Assisted Signal Processing and Thermal Crosstalk - De, Souvaraj; Mandalawi, Younus; Das, Ranjan; Weizel, Maxim (Metrology for THz Communications)
Integrated photonic-assisted signal processing has multiple applications such as signal amplification, multiplexing, and high-Q filtering in optical communication systems, optical sensing systems, and also microwave photonics. We will review recent works on integrated photonic-assisted signal processing for sinc-shaped Nyquist pulse generation, high-bandwidth Nyquist signal detection with low bandwidth devices, arbitrary waveform generation and measurement, and on-chip photonic frequency decoding. However, in such photonic integrated circuits (PICs), the photonic components are placed very close to each other on the chip, resulting in thermal crosstalk which degrades the system performance. Air-filled oxide and deep trench designs have proven to be very effective in mitigating the thermal crosstalk for various frequently deployed photonic devices like Mach-Zehnder modulators (MZMs), ring resonators, optical switches, and photodetectors designed on a standard silicon-on-insulator (SOI) platform. In this chapter, we will additionally review the basics of optical signal processing and some results for such trench-enhanced thermal crosstalk resilient circuits.

Integrated Photonically Assisted Samplers - Weizel, Maxim; Bahmanian, Meysam; Scheytt, J. Christoph (Metrology for THz Communications)
High-speed ADCs operating in the tens of gigahertz up to potentially terahertz range are largely constrained by the jitter in their clock sources. By incorporating photonically assisted samplers that exploit the ultralow jitter of specific mode-locked lasers (MLLs) as analogue ADC frontends, the performance limits of data converters can be pushed to achieve unprecedented levels of accuracy. Continuous advancements in electronic-photonic integration (silicon photonics) are clearing the path for integrating these systems on a chip scale, thereby leading to increased scalability, as well as reduced cost and power consumption.

Simulation and Modelling of Electronic and Photonic Components - Wrana, Dominik; Weizel, Maxim; Haussmann, Simon; Bahmanian, Meysam; Kallfass, Ingmar; Scheytt, J. Christoph (Metrology for THz Communications)
This chapter explores the crucial role of simulation and modelling of electronic and photonic components for terahertz (THz) systems. THz-related challenges already begin with setting up the signal generation and sampling parameters and continue with the realistic modelling of the electronic and photonic building blocks. Hereby, photonic components require not only the modelling of the optical signal propagation but also the modelling of the electronic interface in the THz regime. Furthermore, when advancing to the simulation of systems like fully integrated electronic transmit and receive frontends or photonically assisted analogue-to-digital converters (ADCs), it is up to the designer to find a suitable level of abstraction. Size, complexity, and available computational power versus accuracy must be taken into consideration and prioritized against each other.

Conversion between detector- and rotary-table-related misalignment parameterisations for unified projection-matrix-based geometry calibration in dimensional X-ray computed tomography - Butzhammer, Lorenz (Precision Engineering)

Perspektiven angehender Lehrkräfte auf Forschendes Lernen – eine qualitative Längsschnittstudie im Referendariat und Berufseinstieg - Homt, Martina; Bloh, Bea; Wehde, Janis (Zeitschrift für Bildungsforschung)
Das hochschuldidaktische Konzept des Forschenden Lernens gilt als zentrales Element der universitären Lehrkräftebildung in Deutschland und ist in fast allen Bundesländern Bestandteil des Praxissemesters. Damit einhergehende Erwartungen im Hinblick auf den Professionalisierungsprozess von Lehrkräften fokussieren insbesondere die Vermittlung einer forschenden Grundhaltung, die auf eine nicht-wissenschaftsferne Berufsausübung abzielt. Wir fassen die forschende Grundhaltung als Professionsüberzeugung, die aus einer kognitiven, affektiven und handlungsbezogenen Komponente besteht und untersuchen die Komponenten im Zusammenspiel sowie im Längsschnitt. Mittels teilstrukturierter Interviews mit 22 angehenden Lehrkräften im Referendariat und Berufseinstieg, die sich im Praxissemester mit Forschendem Lernen befasst haben, werden das Verständnis (kognitive Komponente) und die Bedeutsamkeit (affektive und handlungsbezogene Komponente) Forschenden Lernens in der jeweiligen Ausbildungs- bzw. Berufsphase erfragt. Die Daten werden inhaltsanalytisch sowie typenbildend ausgewertet, um das Verständnis und die Bedeutsamkeit in der jeweiligen Phase, längsschnittliche Entwicklungen sowie das Verhältnis von Verständnis und Bedeutsamkeit herauszuarbeiten. Die Befunde zeigen, dass die Verständnisse von Forschendem Lernen sowohl im Referendariat als auch im Berufseinstieg variieren. Zudem ist das Konzept – laut Schilderungen der Befragten – durchaus bedeutsam für ihre Lern- und Handlungspraxis, jedoch nicht für alle und in unterschiedlich ausgeprägter Form. Die Typenbildung verdeutlicht, dass die fehlende Bedeutsamkeit Forschenden Lernens mit Fehlkonzepten einhergeht und eine höhere Bedeutsamkeit erkennbar ist, wenn Adaptionsleistungen hinsichtlich des Konzepts vorgenommen werden. Insgesamt ist im Sinne der Auffassung als Professionsüberzeugung die Anbahnung einer forschenden Grundhaltung bei einigen Befragten erkennbar. Implikationen für eine künftige Hochschulbildung ergeben sich u. a. mit Blick auf die Unterstützung von Studierenden bei Adaptionsleistungen für die (jeweilige) Praxis.